Reproductive potential of four freshwater prawn species in the Amazon region - de Oliveira, Leo Jaime Filgueira [UNESP]; Sant’Anna, Bruno Sampaio; Hattori, Gustavo Yomar (Taylor & Francis, 2017)
The bioecology of freshwater prawns can be understood by studying their reproductive biology. Thus, the aim of this paper was to determine and compare the reproductive potential of four freshwater caridean prawns collected in the Amazon region. For two years, we captured females of Macrobrachium brasiliense, Palaemon carteri, Pseudopalaemon chryseus and Euryrhynchus amazoniensis from inland streams in the municipality of Itacoatiara (AM). At the laboratory, we measured the biometric variables total length, carapace length, abdomen length and total weight, and recorded the number of eggs (NE) by direct counting. There was a significant difference for all variables between the species. The females of M. brasiliense were the most abundant and had the largest sizes and NE. However, the fecundity index shows that P. carteri has the highest reproductive potential of the four species. Despite the differences in size and weight, all the species showed low fecundity, which is a characteristic of continental palemonidean K strategist prawns.
Keywords: Caridea; Euryrhynchidae; fecundity; freshwater prawn; Palaemonidae; reproduction